Activity of the novel T137A SOD1 mutation in amyotrophic lateral sclerosis patients. (July 2012) - Pasini, Elena; de Biase, Dario; Visani, Michela; Morandi, Luca; Danesi, Francesca; Boschetti, Elisa; Tugnoli, Vitaliano; Salvi, Fabrizio; Bordoni, Alessandra; Pession, Annalisa
Aim: More than 160 mutations in the Cu/Zn superoxide dismutase 1 ( SOD1 ) gene are known and identifiable in approximately 20% of patients with familial history of amyotrophic lateral sclerosis (ALS) and in the 1–2% of the sporadic cases. A new SOD1 variant, the T137A missense mutation, was recently discovered. The aim of this study was to better clarify the activity of T137A-SOD1 in ALS patients.Methods: The activity of erythrocyte SOD enzyme and the plasma total antioxidant capacity were measured in 20 ALS patients with wild-type SOD1, in five ALS-patients harboring mutated SOD1 and in seven healthy controls.Results: Erythrocyte Cu/Zn-SOD activity was significantly lower in mutated patients than in wild-type participants and in controls, regardless of the type of mutation. Our data demonstrate that the SOD1 enzyme harboring the novel T137A mutation presents typical features of other known SOD1 variants.Conclusion: These results provide further evidence of the possible pathogenic role of the T137A mutation in ALS.